Work-Life Balance, Job Satisfaction, and Job Performance of SMEs Employees: The Moderating Role of Family-Supportive Supervisor Behaviors - Susanto, Perengki; Hoque, Mohammad Enamul; Jannat, Taslima; Emely, Bamy; Zona, Mega Asri; Islam, Md Asadul (Frontiers in Psychology, 2022)
Even though studies on work-life balance and family-supportive supervisor behaviors are prevalent, there are few studies in the SME setting, and the implications are yet unexplained. Thus, the study examines the effect of work-life balance on the performance of employees in SMEs, along with the mediating role of job satisfaction and the moderating role of family-supportive supervisor behaviors. We have developed a conceptually mediated-moderated model for the nexus of work-life balance and job performance. We collected data from SMEs and employed SEM-PLS to test the research hypothesis and model. Empirical results demonstrate that work-life balance positively influences job satisfaction and performance. Our empirical findings also revealed that job satisfaction partially mediates the relationship between work-life balance and job performance. We also found that when FSSB interacts with work-life balance and job satisfaction, it moderates the relationship between work-life balance and job performance and job satisfaction and job performance. Hence, our findings provide exciting and valuable insights for research and practice.